Optimizing solar performance of CFTSe-based solar cells using MoSe2 as an innovative buffer layers - Mohamed Moustafa; Ziad Abu Waar; Shadi Yasin (Scientific Reports, 2025)
Abstract In this study, we explore the photovoltaic performance of an innovative high efficiency heterostructure utilizing the quaternary semiconductor Cu2FeSnSe4 (CFTSe). This material features a kesterite symmetrical structure and is distinguished by its non-toxic nature and abundant presence in the earth’s crust. Utilizing the SCAPS simulator, we explore various electrical specifications such as short circuit current (Jsc), open circuit voltage (Voc), the fill factor (FF), and power conversion efficiency (PCE) were explored at a large range of thicknesses, and the acceptor carrier concentration doping (NA). Our results demonstrate that optimized parameters yield a remarkable PCE of 26.47%, accompanied by a Voc of 1.194 V, Jsc of 35.37 mA/cm2, and FF of 62.65% at a CFTSe absorber thickness of 0.5 μm. Furthermore, the performance of the photovoltaic cell is assessed for the defect levels in the CFTSe absorber and MoSe2 buffer layers. Results indicate that deep defect levels above 1 × 1017 cm− 3 lead to a decrease in Jsc. The study also investigates the effect of operating temperature on cell performance within the 300–500 K range. A notable decline in Voc is observed, likely due to an increase in saturation current, suggesting an interaction between temperature and cell behavior. In this work, we propose a practical CFTSe-based structure that replaces conventional buffer layers, such as CdS, with MoSe2 TMDC as a promising alternative buffer layer, paving the way for more sustainable solar technology.